The Edge of the Swamp : A Study in the Literature and Society of the Old South - Rubin, Louis D., Jr. (Louis Decimus), 1923-2013 (Book collections on Project MUSE., 1989)
The flowering of literary imagination known as the American Renaissance had few roots in the South. While Hawthorne, Emerson, Melville, Thoreau, and Whitman were creating a body of work that would endure, the only southern writer making a lasting contribution was Edgar Allan Poe. This failure on the part of antebellum southern writers has long been a subject of debate among students of southern history and literature. Now one of the region's most distinguished men of letters offers a cogently argued and gracefully written account of the circumstances that prevented early southern writers from.